Bird Communities And Feeding Guilds From Three Land Use Types In Kerian River Basin, Perak - Azman, Nur Munira (2012)

(untitled)
Land conversion activity has caused losses in a vast number of bird species. Bird status in secondary forest (SF), oil palm plantation (OP) and paddy fields (PF) were documented from March 2009-February 2010 at study sites in Kerian River Basin (KRB). The objectives of this study were to determine the current bird species present in the study areas, to analyze variation of feeding guilds in different habitat types and to identify suitability area for selected threatened bird species. Point count and mist-netting methods were used for bird census in SF and OP, while only point count method was used in PF. Feeding guilds were determined for each species recorded.